2022
DOI: 10.1136/bmjopen-2022-061893
|View full text |Cite
|
Sign up to set email alerts
|

Safety and performance of oropharyngeal muscle strength training in the treatment of post-stroke dysphagia during oral feeding: protocol for a systematic review and meta-analysis

Abstract: IntroductionDysphagia is a common functional disorder after stroke. Most patients post-stroke are incapable of oral feeding, which often leads to complications such as malnutrition, aspiration pneumonia and dehydration that seriously affect the quality of life of patients. Oropharyngeal muscle strength training is a major method of swallowing training, and recent studies have focused on healthy adults, elderly persons, and patients with head and neck cancer or neurodegenerative diseases; but there have been fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The primary objective of treating dysphagia is to reduce the frequency of aspiration and increase oral feeding [ 23 ]. In the examined population, the feeding methods of the stroke patients were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of treating dysphagia is to reduce the frequency of aspiration and increase oral feeding [ 23 ]. In the examined population, the feeding methods of the stroke patients were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis was conducted under the guidance of the Cochrane Handbook for Systematic Reviews of Interventions25 and reported according to the update Preferred Reporting Items for Systematic Reviews and Meta-Analysis,26 26 as well as the research protocol we developed 27. The protocol for this study is available online.…”
Section: Methodsmentioning
confidence: 99%
“…Two researchers (HW and JS) independently screened the literature titles and abstracts according to the research protocol, 27 eliminated literature that did not meet the selection criteria and independently reviewed the full texts of the remaining literature before finally confirming inclusion. Any disagreement should be resolved in consultation with a third reviewer (FZ).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 13.7 million people worldwide experience stroke each year, and almost half of these people experience varying degrees of functional impairment that seriously affects their quality of life. OD is a prevalent disorder after stroke: it occurs in about 80% of cases [5]. OD can lead to dehydration, malnutrition, and aspiration, which can lead to respiratory infections and pneumonia.…”
Section: Introductionmentioning
confidence: 99%